Heart rate response during cardiopulmonary exercise in the denervated heart - Ryohei Ono; Togo Iwahana; Hirotoshi Kato; Yoshio Kobayashi (Clinical Case Reports, 2023)
Abstract The patients after heart transplantation usually present resting tachycardia, a slower increase in heart rate (HR) at the onset of exercise, a blunted chronotropic response to exercise in general, maximal HR being attained in the recovery period rather than at peak exercise, and a slower decline in HR after exercise.